Analisis Kinerja Dan Efisiensi Energi Mesin Water Cooled Chiller Di Gedung Capital Place Tower Jakarta - ASRI, ASRI; Komarudin, Komarudin (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2025)
This study aims to calculate the COP (Coefficient of Performance) value of the chiller and determine whether the value is better than the standard value. The analysis includes taking data on temperature, pressure, evaporator and condenser water flow, amperage and voltage in the compressor on the chiller, then calculating the COP to determine the efficiency of the chiller machine performance. The results of the calculation state that the highest COP value of chiller No. 2 is 7.4 and the lowest is 7.0 in the efficient category referring to the chiller standard of 7.22. While the highest COP of chiller no. 3 is 7.4 and the lowest is 5.1 in the inefficient category referring to the chiller standard of 7.22. The results of the calculation of the capacity of chiller No. 2 at 100% compressor load, the resulting cooling capacity is only 77.29-90%, the potential for increasing efficiency that can be optimized in chiller No. 2 is 22.71-39.38%. Chiller No. 3 at 100% compressor load produces only 83.34-66.89% of the cooling capacity, while the potential efficiency increase that can be optimized in chiller No. 3 is 33.11-37%. To increase chiller efficiency, set the chilled water temperature setpoint not too low between 7-80C adjusted to actual needs, load changes and environmental conditions.